Modeling Multiphase Materials Processes Gas-Liquid Systems - Iguchi, Manabu; Ilegbusi, Olusegun J.; SpringerLink (Online service) (New York, NY : Springer New York : Imprint: Springer, 2011)
Modeling Multiphase Materials Processes: Gas-Liquid Systems describes the methodology and application of physical and mathematical modeling to multi-phase flow phenomena in materials processing. The book focuses on systems involving gas-liquid interaction, the most prevalent in current metallurgical processes. The performance characteristics of these processes are largely dependent on transport phenomena. This volume covers the inherent characteristics that complicate the modeling of transport phenomena in such systems, including complex multiphase structure, intense turbulence, opacity of fluid, high temperature, coupled heat and mass transfer, chemical reactions in some cases, and poor wettability of the reactor walls. Also discussed are: -Solutions based on experimental and numerical modeling of bubbling jet systems -Recent advances in the modeling of nanoscale multi-phase phenomena -Multiphase flows in micro-scale and nano-scale channels and reactors Modeling Multiphase Materials Processes: Gas-Liquid Systems will prove a valuable reference for researchers and engineers working in mathematical modeling and materials processing.
Keywords: Engineering; Engineering mathematics; Surfaces (Physics).; Engineering; Appl.Mathematics/Computational Methods of Engineering; Surfaces and Interfaces, Thin Films; Engineering Thermodynamics, Heat and Mass Transfer